Pharmacological interventions for the prevention of bleeding in people undergoing elective hip or knee surgery: a systematic review and network meta‐analysis - Estcourt, L; Palmer, A; Gibbs, V; Champaneria, R; Doree, C (Wiley, 2019)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the relative efficacy of pharmacological interventions for preventing blood loss in elective primary or revision hip or knee replacement, and to identify optimal administration of interventions regarding timing, dose and route.